HIV AIDS-Medico Legal Point of View - Wasnik, Dr. Sumedh; Sulakhe, Dr. Vaibhav; Ghodke, Dr. Anita; Vaidya, Dr. Nilam (Journal of Medical Biomedical and Applied Sciences, 2018)
Now a day, AIDS is the most burning issue of public health before medical world. Everyone is thinking about its every aspect.  AIDS awareness is increasing day by day among the public, hence the ethical, legal and regulating issues are in focus. In developing country like India, every  effort is made to protect individual rights while safeguarding the public from a fatal communicable virus .There are many unprecedented legal question in public health, education employment, insurance, medical law, family law, civil rights  about HIV AIDS. Presently, there is no legislation particularly integrating all issues concerning HIV & AIDS. Without respect for the human rights, fundamental freedom and the dignity of human beings, there will be no valid treatment for the said disease. Effective prevention, care and support for HIV/AIDS is possible in an environment where human rights are respected and where those infected or affected by HIV/AIDS live a life without stigma and discrimination. The protection of human rights is essential to safeguard human dignity in the context of HIV/AIDS. All possible efforts should be made to train all medical, paramedical and other auxiliary medical health care workers to aware about environment where HIV/AIDS patients are admitted and treated without any fear & scare so that the patients donât feel guilty and get ready for the treatment.